الإعلام و دوره في حماية البيئة (Journal of Humanitarian and Applied Sciences, 2023)
Abstract:The media is one of the most prominent contemporary methods and means, which in turn contributes effectively in showing the most important pressures that man exert on the environment and its components, as well as in increasing the knowledge of the spread of accidents and natural disasters to which they are exposed. The interested in this aspect, whether from the media side or from the environmental sciences side, affirm that the media is of great importance in keeping pace with and knowing a lot of what the environment and its components are exposed to. Therefore, this paper, shed lights on the importance of the various media and the extent of which they are optimally employed to contribute in addressing issues and problems related to the environment within a clear and transparent framework for specialized bodies and institutions concerned with environmental affairs far from private goals and away from personal purposes in the shadow of documented media platforms that select information from their sources in a scientific way, from the politicization, undermining and obscuring of correct information regarding the protection of the environment and its components. Consequently , this paper concluded that the need to enhance the role of the media in protecting the environment through the dissemination of laws, legislation and international charters related to the protection of the environment, as well as using appropriate professional art supported by sound, live image, expressive graphics, and accurate statistics in order to spread environmental awareness among citizens, as well as focus on conducting seminars and scientific conferences and hosting specialists in the field of environmental sciences to increase the culture of environmental protection.